PENGENDALIAN PERSEDIAAN BAHAN BAKU BERAS DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) MULTI PRODUK GUNA MEMINIMUMKAN BIAYA (Studi Kasus PADA CV. Lumbung Tani Sejahterah) - Herlambang, Andini Ika Puspita; Dewi, Rina (JEB17 : Jurnal Ekonomi dan Bisnis, 2017)
ABSTRACTRaw material inventory control is the most important thing, cause raw material is one factor that secure the facilitation of production process. Raw material inventory intended to fulfill the need of standard substance for the production process in the coming day. This need of raw material be calculated on the basis of estimation which affect the raw material purchase pattern and the extent of safeguard inventory. The activities of raw material inventori control set on the implementation of raw material provision required compatible with the quantity that needed along with minimum cost, that is involved material purchasing matters, storing and maintain the material, setting the material output when it required and also protecting the inventory under optimal quantity.Â Keyword : Control, raw material, EOQ, cost.